Impaired cytolytic activity of asthma-associated natural killer cells is linked to dysregulated transcriptional program in energy metabolism. (September 2018) - Wu, Haisi; Bi, Jiacheng; Wu, Gaohui; Zheng, Chaoyue; Lu, Zhen; Cui, Lulu; Wan, Xiaochun
Highlights: Asthma -associated NK cells showed impaired cytolytic activity. Asthma -associated NK cells were hypofunctional in critical steps in cytotoxicity. Asthma -assoiciated NK cells displayed an enrichment of OXPHOS genes. Abstract: Natural killer (NK) cells are a cytotoxic subset of the innate lymphoid cells, playing essential roles in host defense against tumors and infections, which, however, are usually functionally compromised in chronic diseases. Atopic diseases, such as allergic asthma, characterized by type 2 immune responses, are usually associated with chronic inflammations. Whether asthma -associated immune environment affects the cytolytic function of NK cells has not been elucidated. Here, YTS, a human NK cell line, was exposed to serum from healthy donors or asthma patients for analysis of its cytolytic function. We found that, serum from asthma patients reduced the cytolytic activity of YTS cells against Raji human B lymphoblasts, in comparison with normal serum. The impairment of cytolytic activity of these YTS cells was accompanied with decreased degranulation potentials, weakened conjugation formation with Raji cells, and premature termination of ERK phosphorylation upon stimulation. Meanwhile, apoptosis or cell death of YTS cells was not increased after exposure to serum from asthma patients. Importantly, such impairment of cytolytic activity of asthma -associated YTS NK cells was accompanied with aberrantly enriched genes involved in oxidative phosphorylation. Taken together, these results demonstrate that the serum of asthma patients directly suppresses the cytolytic function of NK cells, possibly through dysregulation of energy metabolism in NK cells.